The BETA® nursing measure: Its development and testing for nursing utility - Hendrik J. Loubser; Judith C. Bruce; Daleen Casteleijn (AOSIS, 2013)
In the specialised nursing fields of rehabilitation, convalescence and gerontology requiring restorative nursing interventions, nurses are unable to measure, assess and evaluate accurately and routinely the outcomes of their patients' activities of daily living (ADLs) due to the lack of validated nursing measures. The purpose of this study was to develop a nursing scale, named the BETA, which can be used routinely and embedded into the nursing process and care plan, enabling the primary nursing carer to measure, assess and evaluate patients' ADLs. The first objective was to design and develop the BETA, a routine nursing scale, whereby caregivers and nursing auxiliaries can observe, score and record their patients' activities of daily living. The second objective was to test the BETA's nursing utility to be used routinely. Two qualitative studies were done sequentially. Firstly, individual interviews were conducted to collect descriptive data from registered nurses (n = 6), nursing assistants, (n = 8) and caregivers (n = 16), skilled in the field of restorative care. In the first study, the data were analysed using inductive content analysis techniques to design and construct the BETA nursing measure. In the second study, the BETA's nursing utility was studied by means of the training of and testing the application of the BETA by a new team of professional nurses (n = 6) and caregivers (n = 48) working in a geriatric frail care unit. After 6 months, two homogenous focus groups consisting of registered nurses (n = 3) and caregivers (n = 5) representing this team were interviewed to explore the BETA's nursing utility. Descriptive data in the second study were analysed using deductive content analysis. The initial results were promising. The high levels of agreement on its acceptance, usefulness and confidence, to be used routinely as a nursing scale, confirmed the BETA's nursing utility. The BETA nursing scale has the potential to introduce restorative nursing as a new specialisation field in South African nursing, a much needed service required by patients and multidisciplinary teams. This, however, will depend on the construct validity of the BETA, a study to be reported on in a follow-up article. Gespesialiseerde verpleging vir rehabilitasie, herstelling en gerontologie benodig restoratiewe intervensies, maar verpleegsters kan nie die uitkomste van hul pasiënte se aktiwiteite van daaglikse lewe (ADLs) akkuraat en geroetineerd meet, assesseer en evalueer nie, asgevolg van 'n gebrek aan geldige meet instrumente. Die doel van hierdie studie was om die BETA, 'n verplegings meet skaal, te ontwikkel wat roetineweg deel kan word van die verplegingsproses en sorgplan en wat die primêre versorger in staat stel om pasiënte se ADLs te meet, assesseer en evalueer. Die eerste doelwitte was om die BETA skaal te ontwerp en ontwikkel vir primêre versorgers om hul pasiënte se ADLs roetineweg te kan waarneem en opteken. Die tweede doelwit was om die BETA skaal se nuttigheid vir verpleegsters te toets. Daar is twee opeenvolgende kwalitatiewe studies gedoen. Eers is daar individuele onderhoude gevoer om beskrywende data te versamel van geregistreerde verpleegsters (n = 6), verpleegassistente, (n = 8) en versorgers (n = 16), wat bedrewe is in die veld van restoratiewe verpleging. In die eerste studie is die data geanaliseer met behulp van induktiewe inhoudsanalisetegnieke om die BETA skaal te ontwerp en op te stel. In die tweede studie is die BETA se nuttigheid vir verpleging bestudeer deur opleiding en toetsing in die toepassing van die BETA deur ŉ nuwe span geregistreerde verpleegsters (n = 6) en versorgers (n = 48) wat in ŉ versorgingseenheid vir geriatriese verswaktes werk. Na ses maande is twee homogene fokusgroepe gehou, bestaande uit geregistreerde verpleërs (n = 3) en versorgers (n = 5) wat hierdie span verteenwoordig, om die nuttigheid vir verpleging te ondersoek. Beskrywende data in die tweede studie is met behulp van deduktiewe inhoudsanalisetegnieke geanaliseer. Die aanvanklike resultate was belowend. Die BETA se nuttigheidsvlakke vir verpleging het hoë hoogtes van aanvaarding, betroubaarheid en vertroue bevestig. Die BETA-verplegingskaal het die potensiaal om restoratiewe verpleging as ŉ nuwe spesialiseringsveld in Suid-Afrikaanse verpleging te bewerkstellig, ŉ baie nodige diens vir beide pasiënte en multidissiplinêre spanne. Dit sal egter afhang van die geldigheid van die BETA, ŉ studie waaroor daar in ŉ opvolgartikel verslag gedoen sal word.